2009
DOI: 10.1074/jbc.m109.065557
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of the C-terminal DW-motif in Mediating Inhibition of Pyruvate Dehydrogenase Kinase 2 by Dichloroacetate

Abstract: The mitochondrial pyruvate dehydrogenase complex (PDC) is down-regulated by phosphorylation catalyzed by pyruvate dehydrogenase kinase (PDK) isoforms 1-4. Overexpression of PDK isoforms and therefore reduced PDC activity prevails in cancer and diabetes. In the present study, we investigated the role of the invariant C-terminal DW-motif in inhibition of human PDK2 by dichloroacetate (DCA). Substitutions were made in the DW-motif (Asp-382 and Trp-383) and its interacting residues (Tyr-145 and Arg-149) in the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…72 Very recently, PDKII and DCA were crystallized together revealing molecular interactions that explain the relatively specific inhibition of PDKII by DCA. 73,74 Our data using siRNA to inhibit PDKII and PDH in this and our previous work 7 support the fact that DCA works primarily by inhibition of PDKII. It is possible, however, that after chronic DCA therapy PDKII may be downregulated, or compensated by PDK isoforms that are less sensitive to DCA.…”
Section: Phd-independent Inhibition Of Hif1asupporting
confidence: 85%
“…72 Very recently, PDKII and DCA were crystallized together revealing molecular interactions that explain the relatively specific inhibition of PDKII by DCA. 73,74 Our data using siRNA to inhibit PDKII and PDH in this and our previous work 7 support the fact that DCA works primarily by inhibition of PDKII. It is possible, however, that after chronic DCA therapy PDKII may be downregulated, or compensated by PDK isoforms that are less sensitive to DCA.…”
Section: Phd-independent Inhibition Of Hif1asupporting
confidence: 85%
“…Cys-392 is located on the flexible C-terminal tail of PDHK2 next to a conserved DW-motif that is required for partial ordering of the C-terminal tails (Fig. 7A) (26). Oxidative modification of Cys-392 could prevent formation of the L2 binding site, whereas the C392A mutation could allow association of PDHK2 with L2 even under oxidizing conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This experiment demonstrated that both DCA and 8 bind to the same pocket of the enzyme. Given that DCA is a bona fide pyruvate-site inhibitor [1012], we conclude that, as predicted by the computational studies, 8 exerts its inhibitory action by binding to the allosteric pyruvate regulatory site of the enzyme.…”
Section: Resultsmentioning
confidence: 70%
“…Synthetic PDK inhibitors have been discovered for all four binding sites that are large enough to host small organic molecules [1016]. However, dichloroacetic acid (DCA) remained to date the only bona fide pyruvate-site PDK synthetic inhibitor [1012]. …”
Section: Introductionmentioning
confidence: 99%